Characteristics of Pb(Zr0.53Ti0.47)O-3 films deposited by metalorganic decomposition on Pt/Ti/TiO2/polysilicon/Si3N4/Si for piezoelectric microelectromechanical system devices - Kim, JH; Yoon, YS; Polla, DL (JAPAN SOC APPLIED PHYSICS, 1998)
Pb(Zr0.53Ti0.47)O-3 (PZT) films have been deposited on Pt/Ti/SiO2 and Pt/Ti/TiO2/polysilicon/Si3N4/Si substates. In the case of the Pt/Ti/TiO2/polysilicon/Si3N4/Si substrate, there are two different polycrystalline silicon layers. One has been post-thermal annealed at 950 degrees C for 30 min and the other has not had any thermal treatment after the deposition of the polycrystalline silicon. The hysteresis curve, piezoelectric coefficient (d(33)) and dielectric constant of the as-grown film were measured to characterize the electrical properties. Wide angle X-ray diffraction patterns and cross-sectional images of the films were used to investigate the structural properties. The d(33) Of the PZT thin film on substrate A, which was postannealed at 950 degrees C for 30 min after deposition of polycrystalline silicon, was measured to be 158 pm/V by the single beam laser interferometer method. A low frequency relative dielectric constant was 829. Remanent polarization and coercive held of the film on the substrate A were 39.5 C/cm(2) and 65.2 kV/cm, respectively. In addition, the interface of the PZT thin film on substrate A was more dense than that on substrate B, which was not postannealed after the deposition of polycrystalline silicon. This interface structure is very important during a chemical etching step. These results suggested that the substrate A is a very promising structure for microelectromechanical system devices based on the PZT thin film.
Keywords: INTERFEROMETER